The Impact of Bank Health on the Value of Banking Sector Companies Listed on the IDX 2020-2023 - Pamungkas, Atanasius Teguh; Ambarwati, Sri Dwi Ari; Effendi, M Irhas; Razali, Fazlida Mohd; Feriyana, Winda; Ronald, Geraldus Christian (RSF Conference Series: Business, Management and Social Sciences, 2025)
This study analyzes the impact of bank health on firm value using the RGEC framework, which includes Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. Bank health is widely recognized as a crucial determinant of investor confidence and overall financial stability, making its relationship with firm value particularly relevant for the banking sector. The research focuses on banking companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023, a period marked by post-pandemic recovery and increased market uncertainty. An explanatory quantitative method was applied, utilizing financial report data from 47 banks. Based on purposive sampling, a final sample of 36 firms was selected. Multiple linear regression analysis was conducted using SPSS 25 software. The findings reveal that Risk Profile and Capital do not significantly affect firm value, while GCG and Earnings demonstrate a significant positive influence. These results suggest that strong governance practices and profitability are key drivers of investor perception and firm valuation. In contrast, capital adequacy and risk exposure appear to play a less decisive role in market assessments. The regression model is statistically significant (F = 4.603, p = 0.002) but explains only 11.7% of the variance in firm value, indicating that additional factors beyond RGEC contribute to valuation outcomes. Overall, the study emphasizes the significance of GCG and Earnings in enhancing firm value, while also highlighting the need for further research into other financial and non-financial variables that influence investor decision-making in the banking sector.